Pengaruh Beban Kerja, Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Dinas Koperasi, Usaha Kecil Dan Menegah Dan Perdagangan Kota Probolinggo - Wahyuni, Selvia Novita; Hermawan, Dedi Joko; Haidiputri, Trivosa Aprilia Novadiana (Universitas Panca Marga, 2024)
The research aims to determine to what extent the variables of workload, job stress and work environment partially influence the performance of employees in the Department of Cooperatives, Small and Medium Enterprises and Commerce of Probolinggo City. The type of research used is quantitative with a causal associative approach. The variables studied were workload, work stress, work environment and employee performance of the Department of Cooperatives, Small and Medium Enterprises and Commerce of Probolinggo City, with a total of 58 employees interviewed . The method of data analysis from the research results is a quantitative descriptive method using the help of the SmartPLS program in the form of a convergent validity test, a discriminant validity test, a test of reliability, an R square test, a Q square test and a hypothesis test. Test results show that 1) workload (X1) has no significant influence on employee performance of (0.161) with t-statistics (0.884 < 1.96) and p-value of (0.189 > 0.05), 2) job stress (X2) has a significant effect on employee performance of (0.274) with t statistics (2272 <1.96) and P value of (0.012 > 0, 05) and 3) Work environment (X3) has a significant effect on employee performance of (0.254) with t statistics (1.985 < 1.96) and p value of (0.049 > 0.05).